2003
DOI: 10.1081/jas-120019030
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Parent Reports on Quality of Life for Children with Asthma

Abstract: Children and parents often differ in their perceptions of a complex disease such as asthma. This ancillary study of children with mild to moderate asthma that was conducted at four of the eight clinics in the Childhood Asthma Management Program had two aims: (1) to relate quality of life to asthma symptoms, sociodemographic characteristics, child psychosocial adjustment and family social support and (2) to relate agreement between child- and parent-reported quality of life to child age. For this study particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 30 publications
6
64
3
1
Order By: Relevance
“…10,12,[14][15][16][17][18][19][20][21][22] Stress experienced by children or their parents may also have indirect effects on asthma by causing health-compromising behaviors and comorbidities that adversely affect disease management. [23][24][25][26][27][28][29][30][31][32][33][34] Caregiver stress, negative life events, problematic family relationships, parenting difficulties, critical attitudes of one's mother and violence exposure have been related to wheeze, asthma onset, and/or adverse asthma outcomes among infants and youths. 14,15,[20][21][22][29][30][31][32][35][36][37][38][39][40][41] The housing and health relationship has long been acknowledged, not surprising given that water, warmth, air, shelter, and safety are fundamental human needs.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,[14][15][16][17][18][19][20][21][22] Stress experienced by children or their parents may also have indirect effects on asthma by causing health-compromising behaviors and comorbidities that adversely affect disease management. [23][24][25][26][27][28][29][30][31][32][33][34] Caregiver stress, negative life events, problematic family relationships, parenting difficulties, critical attitudes of one's mother and violence exposure have been related to wheeze, asthma onset, and/or adverse asthma outcomes among infants and youths. 14,15,[20][21][22][29][30][31][32][35][36][37][38][39][40][41] The housing and health relationship has long been acknowledged, not surprising given that water, warmth, air, shelter, and safety are fundamental human needs.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Given that HRQoL in children and adolescents is the object of our study, there is a wide range of possibilities to assess it because proxy questionnaires can be applied to children and adolescents who have limiting conditions and also to those with reading comprehension d i f f i c u l t i e s o r w h o h a v e a l o w socioeconomic level. In this regard, parents are fundamental to assess their children's HRQoL 10 and make critical contributions to treatment-related decisions that will be implemented by physicians and specialists, 11,12 and to detect changes over time in their children's HRQoL. 13 However, the assessment made by a proxy may never replace the child/patient who could perform it correctly because they provide a more accurate assessment of psychosocial domains.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of youth with epilepsy and asthma, child-parent agreement has been reported to increase with the child's age. 42,43 Future secondary analysis of data collected with this project will include the parental reports of health status and QOL. …”
mentioning
confidence: 99%